IMPROVEMENT IN IMAGING BELOW SHALLOWGAS CLOUD USING SEISMIC MULTIPLES - MAD ZAHIR, MOHAMAD HAFIZAL (2020)
In Malaysian Basins, offshore Malaysia, there are many seismic imaging issues related to the shallow anomalies so-called ‘gas cloud’ or ‘gas chimney’. Gas cloud consists of gas bearing sediment, has always been a great challenge to acquiring good seismic image of the subsurface. The seismic velocity field is severely complicated by the presence of the gas-filled sediments, which produces strong multi-pathing and complex travel time delays. The heterogeneous nature of these gas-filled areas results in scattering, dispersion, internal multiples, mode conversion during wave propagation through the heterogeneous zone and possibly inelastic losses. All these effects lead to significant deterioration of the seismic image in terms of amplitude attenuation and strong lateral variation of the seismic velocities.